Complementary group Metacognitive Training (MCT) reduces delusional ideation in schizophrenia - Moritz, Steffen; Veckenstedt, Ruth; Bohn, Francesca; Hottenrott, Birgit; Scheu, Florian; Randjbar, Sarah; Aghotor, Julia; Köther, Ulf; Woodward, Todd S.; Treszl, András; Andreou, Christina; Pfüller, Ute; et al. (Schizophrenia research, 2013)
Background - Symptom reduction under antipsychotic agents is incomplete for most schizophrenia patients. In order to enhance outcome, cognitive approaches are increasingly adopted as add-on interventions. The present study aimed to determine the efficacy of group Metacognitive Training (MCT), which targets cognitive biases putatively involved in the pathogenesis of delusions. - Methods - A two-center, randomized, assessor-blind, controlled trial between MCT group training and cognitive training was carried out (ISRCTN95205723). A total of 150 in- and outpatients with DSM diagnoses of schizophrenia spectrum disorders were enrolled. All patients were concurrently prescribed antipsychotic medication. Assessments were made at baseline, four weeks and six months later. The primary outcome was a delusion score derived from the Positive and Negative Syndrome Scale (PANSS). The Psychotic Symptom Rating Scales (PSYRATS) as well as cognitive measures served as secondary outcomes. - Results - Completion at follow-up was 86%. According to intention-to-treat (ITT) analyses, patients in the MCT group showed significantly greater symptom reduction on the PANSS delusion subscore (follow-up), PANSS positive score (post-treatment) and PSYRATS delusion score (post-treatment and follow-up). Improvement on the PANSS positive scale at post-treatment and follow-up was positively correlated with the number of attended MCT sessions. No changes were seen for other psychopathological syndromes. - Discussion - MCT, a low-intensity training aimed at enhancing patients' awareness of cognitive biases subserving paranoia, led to improvement in delusion symptoms relative to the control condition and over and above the effects of antipsychotic medication. This improvement was sustained at follow-up.
Gesehen am 09.06.2021